Baryon breakdown in black hole - Lehmonen, Lauri; Annila, Arto (Frontiers in Physics, 2022)
According to relativity theory, a black hole is a distinct region in spacetime; according to astronomical observations, it is a celestial body transforming matter into high-energy jets. We propose that a black hole is, indeed, a star, where particles transform into photons through a specific nuclear reaction, besides radiative accretion disk processes. Our reasoning draws from statistical physics of open quantized systems. The many-body theory describes elementary particles comprising quanta of actions and their reactions as conversions of matter-bound quanta into vacuum quanta. The proposed transformation details the annihilation of neutrons into gamma rays. This reaction, characteristic of a black hole, begins when the strength of gravitation exceeds the strength of the strong force. Then gluons detach from quarks and attach to surrounding high-energy quanta of the gravitational field. Without gluons, the tightly packed neutrons cannot hold up their SU(3) symmetry. The tetrahedral structures flatten out so that quarks of opposite charges end up pairwise on top of each other and annihilate into rays of light quanta as electrons and positrons do. Finally, the quanta jet out along the black hole spinning axis, where the gravitation due to the collapsing core gives in most. Over the eons, these episodic effluxes from a precessing supermassive black hole amass into Fermi bubbles.